Attentional bias toward and distractibility by sexual cues: A meta-analytic integration. (October 2019) - Strahler, J.; Baranowski, A.M.; Walter, B.; Huebner, N.; Stark, R.
Highlights: Sexual cues bias and divert attention but the actual extent remains unclear. Greater attentional bias for sexual cues is assumed in men. 32 studies provided 49 effects sizes with 13 studies examining gender differences. Attentional bias to and distractibility by sexual cues was less than expected ( g z  = 0.49). Results implicated higher attentional bias/interference in men ( g s  = 0.28). Abstract: From an evolutionary perspective, sexual stimuli are highly salient and are assumed to be processed with high priority. Hence, attentional processing of sexual cues is expected to not only bias attention but to also distract from other cognitive (foreground) tasks. It is, however, unclear to what extent these stimuli capture attention and whether there are differences between men and women. This meta-analysis combined the results of 32 studies employing experiments of attentional bias toward and distraction by sexual stimuli. From these, 13 studies provided data to examine gender differences. Overall, attentional bias and distractibility was lower than anticipated ( g z  = 0.43, p  < .001) and there was support for the assumption of higher attention bias/interference in men ( g s  = 0.29, p  = .031). Importantly, there was evidence for the presence of publication bias. With this in mind, findings are discussed in the context of stimulus features, the impact of provoked sexual arousal and motivational state, and gender-specific and -nonspecific neural processing of sexual stimuli which influence attention toward them.